Morphology of caterpillars and pupae of European Maculinea species (Lepidoptera: Lycaenidae) with an identification table - Śliwińska, Ewa; Nowicki, Piotr; Nash, David; Witek, Magdalena; Settele, Josef; Woyciechowski, Michal (Entomologica Fennica, 2006)
Ofthe four recognized Maculinea species that occur in Europe, three (M. teleius, M. nausitlzous, and M. alcon) are found on damp meadows, and may co-occur; sometimes their larval instars even occupy the same host ant nest. It is, therefore, important to be able to distinguish between the caterpillars of these species for effective conservation. We present the morphology of the larvae and pupae of these three species, and a simple key to their identification. Inter-specific differences among larvae and pupae, and within-species differences among larval instars, are underlined in order to enable their proper identification. The length, colour and distribution of bristles are considered the best features for species and instar identification. The morphology ofthe described species is compared with that of the other European species, M. arion.